1981
DOI: 10.1021/bi00504a012
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of formation of pyrimidine dimers in SV40 chromatin in vitro

Abstract: The efficiency of formation of pyrimidine dimers by 254-nm light was studied in mixtures of SV40 chromatin and DNA extracted from that chromatin. At high doses (beyond 380 J/m2), fewer dimers are formed in chromatin than in DNA for a given dose of radiation. This difference is about 10% as saturation with pyrimidine dimers is approached at 6840 J/m2. Conversely, at biologically repairable doses (up to 40 J/m2, less than 2 dimers/genome), significantly more dimers are produced in the chromatin than in the DNA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1982
1982
1987
1987

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Indeed, Hanawalt and coworkers have shown that the yield of PD in a DNA of African green monkey cells and amplified DNA in Chinese hamster cells (containing the transcriptionally active dihydrofolate reductase gene) is very similar to the yield determined for the bulk of the DNA in chromatin (8,9). Studies have also been performed at the nucleosome level of chromatin, focusing on the distribution of PD between nucleosome core DNA and linker DNA (11)(12)(13). The results ofthese studies indicate that the distribution of PD is essentially uniform between these two regions of the nucleosome unit at low to moderate UV doses.…”
mentioning
confidence: 96%
“…Indeed, Hanawalt and coworkers have shown that the yield of PD in a DNA of African green monkey cells and amplified DNA in Chinese hamster cells (containing the transcriptionally active dihydrofolate reductase gene) is very similar to the yield determined for the bulk of the DNA in chromatin (8,9). Studies have also been performed at the nucleosome level of chromatin, focusing on the distribution of PD between nucleosome core DNA and linker DNA (11)(12)(13). The results ofthese studies indicate that the distribution of PD is essentially uniform between these two regions of the nucleosome unit at low to moderate UV doses.…”
mentioning
confidence: 96%
“…Unlike furococoumarin adducts, the pyrimidine dimers produced by UV,,, are located both in cores and linkers. At biologically relevant doses, the pyrimidine dimer frequency per unit DNA may even be higher in the nucleosome cores than in linker DNA [56].…”
Section: Role Of Chromatin Structure In Dna Repairmentioning
confidence: 99%
“…Williams and Friedberg (1979) irradiated human cells and found no difference between total DNA and the nucleosomal core particles in the yield of thymine-containing dimers, measured by thin layer chromatography. Snapka and Linn (1981) irradiated in vitro mixtures of SV40 chromatin and DNA [in the presence of 10 mM Tris-C1 (pH 7.5). 0.13 M NaCI, 0.2 mM EDTA.…”
Section: Discussionmentioning
confidence: 99%
“…After a further 10 min, the lysed cells were scraped into centrifuge tubes, held on ice 30 min, and pelleted (10000 rpm, 5 min, Sorvall RC2B); the supernatant contains SV40 chromosomes. Snapka and Linn, 1981). Dishes were rinsed twice with PBSd.…”
Section: Triton Extraction (Green and Brooks 1976) Dishesmentioning
confidence: 99%
See 1 more Smart Citation